2015
DOI: 10.33762/eeej.2015.102733
|View full text |Cite
|
Sign up to set email alerts
|

A comparative Study of Forecasting the Electrical Demand in Basra city using Box-Jenkins and Modern Intelligent Techniques

Abstract: The electrical consumption in Basra is extremely nonlinear; so forecasting the monthly required of electrical consumption in this city is very useful and critical issue. In this Article an intelligent techniques have been proposed to predict the demand of electrical consumption of Basra city. Intelligent techniques including ANN and Neuro-fuzzy structured trained. The result obtained had been compared with conventional Box-Jenkins models (ARIMA models) as a statistical method used in time series analysis. ARIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…(2015) studied the monthly electrical consumption in Basra (January 2005 to December 2011) by Auto-Regressive Integrated Moving Average (ARIMA) model and two layered feed forward artificial neural network (ANN) with 12 neurons in the hidden layer, and finally an adaptive neuro-fuzzy inference system (ANFIS) model [29]. They managed the mean absolute errors (MAE) of 0,31604 (Box-Jenkins ARIMA), 0,301 (ANN), and 0,2491 (ANFIS) [29]. Arfoa (2015) studied the maximum load (2005 to 2013) (MW) and forecasted peak load demand (2014 to 2023) in Ma'an, Karak and Aqaba in Jordan by least squares method [27].…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…(2015) studied the monthly electrical consumption in Basra (January 2005 to December 2011) by Auto-Regressive Integrated Moving Average (ARIMA) model and two layered feed forward artificial neural network (ANN) with 12 neurons in the hidden layer, and finally an adaptive neuro-fuzzy inference system (ANFIS) model [29]. They managed the mean absolute errors (MAE) of 0,31604 (Box-Jenkins ARIMA), 0,301 (ANN), and 0,2491 (ANFIS) [29]. Arfoa (2015) studied the maximum load (2005 to 2013) (MW) and forecasted peak load demand (2014 to 2023) in Ma'an, Karak and Aqaba in Jordan by least squares method [27].…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…In [1], the author proposed an autoregressive moving average model with an exogenous weather variable (ARMAX) to forecast short-term electrical loads (next 24 hours) using cargo results show that the mean absolute percentage error (MAPE) ranges from 3.01 to 4.54%. The comparative study of electricity demand forecast of Basra, Iraq using Box-Jenkins method and artificial neural network (ANN) was reported [2]. The obtained results have shown that using ANN improves the accuracy of the forecast.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the human population and the development and application of technology has resulted in a rapid increase in electrical energy consumption. As a result, predicting electrical energy consumption is required when making electrical energy management decisions [1]. Predicting electricity consumption is critical for developing-country governments especially to improve energy efficiency.…”
Section: Introductionmentioning
confidence: 99%